Scribner Encyclopedia of American Lives, Vol. 5 (1997-1999) (New York Charles Scibner's Sons, 2002)
Each volume of this series contains biographies of famous Americans in all walks of life covering specific years, listed alphabetically.
lncludes occupations index and alphabetical listing of subjects.
79221
Keywords: Famous persons -- Biography -- Dictionaries - encylopedias; United States